Reconstructing State Loss Recovery Mechanisms for Good Governance Resulting from Abuse of Authority in Environmental Management in Indonesia - Fitria, Fitria; Abd Aziz, Hartinie; Helmi, Helmi; Pratiwi, Cholillah Suci; Kamil, Azahery Insan (Faculty of Law, Jambi University, 2025)
This paper addresses the main question of how state loss recovery mechanisms in Indonesia can be reconstructed to ensure good governance in cases of abuse of authority in environmental management. The background of the study lies in the persistent problem of environmental degradation caused by defective licensing practices, corruption, and weak institutional coordination, which result not only in financial losses to the state but also in significant ecological damage. The research adopts the position that the prevailing legal framework remains overly focused on cash losses and fails to adequately recognize ecological losses as part of state economic losses. Using a normative legal research method with statutory, conceptual approaches, this study examines Indonesian regulations and draws comparative insights from Malaysia to highlight shared governance challenges in recovering state losses arising from environmental mismanagement. The analysis demonstrates that fragmented enforcement across administrative, civil, criminal, and financial law weakens accountability and hampers effective recovery. The main result of the study is the formulation of a reconstructed model of state loss recovery that integrates ecological valuation, asset recovery, and the establishment of a dedicated environmental restoration fund. This model is expected to strengthen legal certainty, institutional coordination, and the realization of good governance in environmental management.